PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STAD DALAM PENGEMBANGAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - M. Taufik (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
One porpuse of social studies teaching in elemntary school is to develop social skill. the aim of research is to know how effec cooperative learning to increas social skills of studens.this research it used quasi-experimental methods.The data collecting technique in this research is observation, interview and questionare. The result of research describe, the social studies learning with cooperative learnig models STAD provides a positive effect on  the development of student’s social skills.the cooperative learning models STAD can use in social studies learning to develop social skill of students.Keyword: social studies, cooperative learning